The Family Church in the epidemic and the reflection on the Last Generation: taking the Family Church in a certain area of a city as an example - CUI, Renzhong (Journal of Research for Christianity in China (JRCC), 2025)
The outbreak of the COVID-19 epidemic is a heavy test for the Chinese people, production, life and other aspects have been seriously impacted and destroyed, and the normal belief activities of the house church have also been blocked. During the duration of the epidemic, the family church carried out a series of measures to deal with the epidemic based on the basic principles of abiding by government management, conserving basic beliefs and caring for brothers and sisters. Now that the epidemic has been partially alleviated, it is of practical significance to review the measures taken by the family church in the epidemic. Therefore, this paper uses the example of the house church in a certain area of a city as an observation point to study the response of the house church to the epidemic situation of COVID-19 in all parts of the country. In addition, because of the similarities between the epidemic situation and the records of the last generation in the Bible, this paper puts forward some thoughts on the personal belief behavior and ideas of the last generation, the handling of the relationship between man and nature, freedom of belief and the rule of law.